2020
DOI: 10.1177/0003122420957249
|View full text |Cite
|
Sign up to set email alerts
|

School Outcomes of Children Raised by Same-Sex Parents: Evidence from Administrative Panel Data

Abstract: Although widely used in policy debates, the literature on children’s outcomes when raised by same-sex parents mostly relies on small selective samples or samples based on cross-sectional survey data. This has led to a lack of statistical power and the inability to distinguish children born to same-sex parents from children of separated parents. We address these issues by using unique administrative longitudinal data from the Netherlands, which was the first country to legalize same-sex marriage. These data inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 70 publications
0
22
0
2
Order By: Relevance
“…Because parenthood is rarer for male than for female couples, there is less research on gay fathers than on lesbian mothers (Doucet and Lee 2014;Moore and Stambolis-Ruhstorfer 2013). Among the common themes that emerged in earlier research are identity formation (e.g., Hequembourg and Farrell 1999), the desire to procreate (e.g., Bos et al 2003), paths to parenthood (e.g., Chabot and Ames 2004;Malmquist and Nelson 2014), well-being and school outcomes among children (e.g., Aldén et al 2017;Boertien and Bernardi 2019;Mazrekaj et al 2019), parental stress (e.g., Bos 2010), encounters with health-care providers (e.g., Malmquist 2015), and experiences navigating the legal system (e.g., Compton and Baumle 2015;Park et al 2016). In this chapter, we focus on the division of work and care in same-sex parent families and couples, and examine the extent to which the research findings map onto or challenge traditional family sociological theories and perspectives.…”
Section: Context Theories and Prior Researchmentioning
confidence: 99%
“…Because parenthood is rarer for male than for female couples, there is less research on gay fathers than on lesbian mothers (Doucet and Lee 2014;Moore and Stambolis-Ruhstorfer 2013). Among the common themes that emerged in earlier research are identity formation (e.g., Hequembourg and Farrell 1999), the desire to procreate (e.g., Bos et al 2003), paths to parenthood (e.g., Chabot and Ames 2004;Malmquist and Nelson 2014), well-being and school outcomes among children (e.g., Aldén et al 2017;Boertien and Bernardi 2019;Mazrekaj et al 2019), parental stress (e.g., Bos 2010), encounters with health-care providers (e.g., Malmquist 2015), and experiences navigating the legal system (e.g., Compton and Baumle 2015;Park et al 2016). In this chapter, we focus on the division of work and care in same-sex parent families and couples, and examine the extent to which the research findings map onto or challenge traditional family sociological theories and perspectives.…”
Section: Context Theories and Prior Researchmentioning
confidence: 99%
“…We concentrate on the experiences of children who had opposite-sex parents at birth. Although there might be different processes governing parental involvement in single-sex parented families, most studies have found that children raised in single-sex parented families have similar, or even better, outcomes compared to those raised in opposite-sex parented households (Juros 2017;Mazrekaj et al 2020). We also do not explore outcomes for students who were primarily parented by fathers.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of scholarship has focused on the development of children living with same-sex couples, comparing them to children with similar family structures and sociodemographic backgrounds but with differentsex parents. This work has tended to find either no differences between these groups of children or advantages favoring children raised by same-sex couples (Mazrekaj et al, 2020;Reczek, 2020). Generally, research has identified that after accounting for sociodemographic differences, there are few differences between children raised by lesbian and heterosexual parents including measures of self-esteem, quality of life, psychological adjustment, and social functioning (adams & Light, 2015;.…”
Section: Same-sex Parents and Child Developmentmentioning
confidence: 99%